Basic statistics for the behavioral sciences - Heiman, Gary W. (Belmont, CA : Wadsworth/Cengage, 2014)
Offering a conceptual-intuitive approach, this popular book presents statistics within an understandable research context, deals directly and positively with student weaknesses in mathematics, and introduces new terms and concepts in an integrated way.
Introduction to Statistics -- Statistics and the Research Process -- Frequency Distributions and Percentiles -- Measures of Central Tendency; The Mean, Median, and Mode -- Measures of Variability: Range, Variance, and Standard Deviation -- z-Scores and the Normal Curve Model -- The Correlation Coefficient -- Linear Regression -- Using Probability to Make Decisions about Data -- Introduction to Hypothesis Testing -- Performing the One-Sample t-Test and Testing Correlation Coefficients -- The Two-Sample t-Test -- The One-Way Analysis of Variance -- The Two-Way Analysis of Variance -- Chi Square and Other Nonparametric Procedures.
Includes index.
Keywords: Statistics; Social sciences -- Statistical methods